If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -9 = 14 + -3x Reorder the terms: -9 + 10x = 14 + -3x Solving -9 + 10x = 14 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -9 + 10x + 3x = 14 + -3x + 3x Combine like terms: 10x + 3x = 13x -9 + 13x = 14 + -3x + 3x Combine like terms: -3x + 3x = 0 -9 + 13x = 14 + 0 -9 + 13x = 14 Add '9' to each side of the equation. -9 + 9 + 13x = 14 + 9 Combine like terms: -9 + 9 = 0 0 + 13x = 14 + 9 13x = 14 + 9 Combine like terms: 14 + 9 = 23 13x = 23 Divide each side by '13'. x = 1.769230769 Simplifying x = 1.769230769
| 6x+6=15x^2 | | 8g-40=-58.4 | | (x/3)-1/2=3/4 | | (3c-5)=(c+5) | | -74+5x=86+3x | | K/2×9=30 | | 8x+22=4x+8 | | 2x-3=9x-10 | | 16.6mi+d=26.2 | | (-3)4-52= | | 6v-(5/8)=(7/8) | | logx(7)=1.8 | | 2b-5=-4 | | 2x(5)+4y=140 | | (a/7)+(5/7)=(2/7) | | 10=-10-7m | | y=325-10x | | F/2-16=5 | | 18=1.5+3y | | x^2+5x-10+3x=6x+89 | | x^2+5x-10+5x=6x+89 | | 2secx+8=0 | | .4d+6=42 | | 5/7R-19=-8 | | 7=8v-4(v+8) | | h(3)=-2(3)(3)+(3)-5 | | 1=v+8/15 | | -5(8x+3)=31 | | 7=-13+x | | v+3.6=5.31 | | 14x+14=6x-10 | | h(0)=-2(0)(0)+(0)-5 |